2014
DOI: 10.5455/msm.2014.26.85-89
|View full text |Cite
|
Sign up to set email alerts
|

From Immigrant to Patient: Experiences of Bosnian Immigrants in the Swedish Healthcare System

Abstract: Background: We aimed to explore the background of refugees emigrating to Sweden and their situation in the new country with special focus on their contacts with the Swedish healthcare system. Material and methods: Our study has a qualitative design. Data was collected between January and October 2013 during face-to-face interviews using open-ended questions. A qualitative content analysis was carried out in accordance with the Graneheim and Lundman method (2004). The participants were 8 women and 7 men, aged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Language barriers in relation to patients hinder the provision of therapy and possibly affect compliance with treatment (Grandpierre et al, 2018). When immigrant patients in Sweden experience problems with communication and language, they require help from relatives or interpreters when visiting healthcare establishments (Seffo, Krupic, Grbic & Fatahi, 2014). The provision of relevant interpreters must be supported by the organisations (Balcazar et al, 2009) and be suitable in terms of minority languages and gender, for example (Hultsjö, 2005).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Language barriers in relation to patients hinder the provision of therapy and possibly affect compliance with treatment (Grandpierre et al, 2018). When immigrant patients in Sweden experience problems with communication and language, they require help from relatives or interpreters when visiting healthcare establishments (Seffo, Krupic, Grbic & Fatahi, 2014). The provision of relevant interpreters must be supported by the organisations (Balcazar et al, 2009) and be suitable in terms of minority languages and gender, for example (Hultsjö, 2005).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Finding the best quality of communication using an interpreter is important to reduce miscommunication since language barriers are central risk factors in relation to healthcare for migrants (Hampers et al 1999;Bischoff 2003;Ramirez et al 2008;Bauer & Alegria 2010;Seffo et al 2014;Ventriglio et al 2014;Njeru et al 2015). Good quality of communication is very central to the health of migrated people (Leininger & McFarland 2006), since migration and integration can lead to positive or negative consequences for the health of the individual (Albin et al 2005;Wallace & Kulu 2014;Syse et al 2016).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Misunderstandings because of limited communication are an increasing hindrance to accessing healthcare (Bischoff 2003), and language barriers have shown to be a risk factor concerning migrant people's health and are mentioned by migrant patients as the major problem in contact with healthcare (Seffo et al 2014). Earlier studies in somatic emergency healthcare have shown how language barriers increase risk of misdiagnosis (Hampers et al 1999), lead to limited access to diagnoses, diagnostic testing and treatment (Ramirez et al 2008;Ventriglio et al 2014;) as well as longer stay for the patients at the emergency department (Mahmoud et al 2013;Njeru et al 2015).…”
Section: Language Barriers and Interpreting Practices In Healthcarementioning
confidence: 99%
“…My history, my life is stamped into my heart. ' (Fang, Sixsmith, Lawthom, Mountian, & Shahrin, 2015) In effect these personal factors determine a person's overall life context (Biswas, Kristiansen, Krasnik, & Norredam, 2011;Krupic, Sadic, & Fatahi, 2016;Seffo, Krupic, Grbic, & Fatahi, 2014).…”
Section: Personal Factorsmentioning
confidence: 99%